Angola : Fifth Review Under the Extended Arrangement Under the Extended Fund Facility and Request for Modifications of Performance Criteria-Press Release; Staff Report; and Statement by the Executive Director for Angola. (IMF Staff Country Reports; Country Report, 2021)
Near-term macroeconomic prospects continue to improve in the context of higher oil prices and a gradual global recovery from the pandemic shock, but the medium-term outlook remains challenging and highly uncertain. Oil production remains muted, debt and inflation remain elevated, and non-oil activity is expected to recover only gradually. However, continued strong fiscal performance (aided by higher oil revenues), exchange rate stabilization, and a return to positive non-oil growth would contribute to a reduction in the debt-to-GDP ratio this year, easing debt vulnerabilities.